The effect of endotracheal tubes versus laryngeal mask airways on perioperative respiratory adverse events in infants: a randomised controlled trial. Issue 10070 (18th February 2017) - Drake-Brockman, Thomas F E; Ramgolam, Anoop; Zhang, Guicheng; Hall, Graham L; von Ungern-Sternberg, Britta S
Summary: Background: Perioperative respiratory adverse events (PRAE) are the most common critical incidents in paediatric anaesthesia and occur more often in infants. Use of laryngeal mask airways (LMAs) is associated with reduced PRAE compared with endotracheal tubes in older children (>1 year). We aimed to evaluate the effect of these devices on the incidence of PRAE in infants. Methods: We did a randomised controlled trial at the Princess Margaret Hospital for Children in Perth (WA, Australia) by recruiting infants (aged 0–12 months) undergoing general (with or without regional or local) anaesthesia with anticipated fentanyl dose 1 μg/kg or lower for minor elective surgery. We excluded patients contraindicated for LMA or endotracheal tube; who had known cardiac disease or airway or thoracic malformations; who were receiving midazolam premedication; who were undergoing airway, thoracic, or abdomen surgery at the time of participation; and if the parents did not speak English. Written parental or guardian consent was obtained before enrolment. Participants were randomly assigned (1:1), by computer-generated variable block randomisation, to receive an LMA (PRO-Breathe, Well Lead Medical Co Ltd, Panyu, China) or an endotracheal tube (Microcuff, Halyard Health Inc, Atlanta, GA, USA). Sealed randomisation envelopes were used to conceal device assignment. An interim analysis was planned once half the number of infants needed (145) had been recruited. The primary outcome was incidence of PRAE, assessed in the intention-to-treat population. The institutional ethics committee at the Princess Margaret Hospital for Children granted ethical approval (1786/EP). The trial is registered with the Australian New Zealand Clinical Trials Registry (ACTRN12610000250033). Findings: The trial began on July 8, 2010, and was ended early on May 7, 2015, after the interim analysis results met the study stopping rules. During this time, 239 infants were assessed and 181 eligible infants were randomly assigned to receive an LMA (n=85) or an endotracheal tube (n=95). Four infants were not included in the analysis (two due to cancelled procedures, one did not meet inclusion criteria, and one with missing dataset). In the intention-to-treat analysis, PRAE occurred in 50 (53%) infants in the endotracheal tube group and in 15 (18%) infants in the LMA group (risk ratio [RR] 2·94, 95% CI 1·79–4·83, p<0·0001). Laryngospasm and bronchospasm (major PRAE) were recorded in 18 (19%) infants in the endotracheal tube group and in three (4%) infants in the LMA group (RR 5·30, 95% CI 1·62–17·35, p=0·002). No deaths were reported. Interpretation: In infants undergoing minor elective procedures, LMAs were associated with clinically significantly fewer PRAE and lower occurrence of major PRAE (laryngospasm and bronchospasm) than endotracheal tubes. This difference should be a consideration in airway device selection. Funding: Princess Margaret Hospital Foundation, National Health and Australian Medical Research Council, Stan Perron Charitable Trust, and Callahan Estate.